Зміни в загальних правилах оформлення документів з 01 квітня 2018 року - Анісімова, Ольга (Видавництво Львівської політехніки, 2018)
Changes in the general rules of execution of documents are considered in accordance with the resolution of the Cabinet of Ministers of Ukraine of January 17, 2018, N 55 "Some issues of documenting management activity". A comparative analysis of the main differences from the requirements specified in DSTU 4163-2003 has been carried out.
Keywords: документування; загальні правила; оформлення документів; інструкція з діловодства